Implementasi Akad Murabahah dan Ijarah Muntahiyah Bit Tamlik Pada Produk KPR BRI Syariah KC Malang Kawi - Moch Novi Rifa’i, Winda Ika Pratiwi (FALAH Jurnal Ekonomi Syariah, 2017)
This study aims to explain how the mechanism of mortgage product (KPS) at BRI Syariah. In each bank, there is a different use of the contract on the mortgage product, although the contract used remains based on the contract in accordance with Islamic Sharia. By using interview and survey methods to find out the mechanism of mortgage product at bank BRI Syariah KC Malang Kawi. The result of shows that mortgage product (KPR) in BRI Syariah consists of two kinds: namely mortgage product (KPR) Faedah and ijarah muntahiyah bit tamlik (IMBT); where KPR Faedah using murabahah contract and IMBT using ijarah muntahiyah bit tamlik (IMBT). In the essence, both of two products issued by BRI Syariah are the same, there are only different in working mechanism. In KPR Faedah, the principal installment will be greater each installment period until the end of repayment. While the principal installment of KPR IMBT is fixed from the beginning of the installment period until the end of repayment. The term used also differs between the products KPR Faedah and KPR IMBT; where in KPR Faedah used the term âinstallment marginâ for the benefit of the bank, and on IMBT mortgage product used the term âinstallment ujrahâ.